2011
DOI: 10.1016/j.ymssp.2011.05.014
|View full text |Cite
|
Sign up to set email alerts
|

On impact damage detection and quantification for CFRP laminates using structural response data only

Abstract: The overall purpose of the research is to detect and attempt to quantify impact damage in structures made from composite materials. A study that uses simplified coupon specimens made from a Carbon Fibre-Reinforced Polymer (CFRP) prepreg with 11, 12 and 13 plies is presented. PZT sensors were placed at three separate locations in each test specimen to record the responses from impact events. To perform damaging impact tests, an instrumented droptest machine was used and the impact energy was set to cover a rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(60 citation statements)
references
References 24 publications
0
60
0
Order By: Relevance
“…The fast Fourier transform (FFT) is used to convert the time domain signals to a frequency spectrum of the conditions studied. During the post processing steps, the calculation of the frequency centroid or known as the Damage Index (DI; Sultan et al, 2011) is shown below…”
Section: Resultsmentioning
confidence: 99%
“…The fast Fourier transform (FFT) is used to convert the time domain signals to a frequency spectrum of the conditions studied. During the post processing steps, the calculation of the frequency centroid or known as the Damage Index (DI; Sultan et al, 2011) is shown below…”
Section: Resultsmentioning
confidence: 99%
“…They also identified the location and size of delamination via virtual grids. Sultan et al [109] employed the concept of discordancy from the statistical discipline of outlier analysis, to identify and quantify the damaging and non-damaging impact in smart composite laminates. Frequency centroids were obtained from the transient response clustering and wavelet packet transform (WPT).…”
Section: Othersmentioning
confidence: 99%
“…Damage indices for non-damaged and damaged cases; (solid line) threshold value: a sensor 1, b sensor 2, and c sensor 3[109] Mahalanobis squared distances for non-damaged and damaged cases; (solid line) threshold value[109] …”
mentioning
confidence: 99%
“…Upon low or intermediate velocity impacts the damage inside the target panel could be large and the laminated composite panel can suffer a significant loss of its designed strength sometimes without a visible indication of damage on the impacted surface [4], thus this is considered to be the most detrimental damage; the impact damage being difficult to detect and often leading to a serious reduction of the structural integrity and mechanical properties [5]. Inter-laminar stresses or mismatching of bending stiffness between two adjacent laminate have been suggested as causes of delamination in the composite laminates subjected to low velocity impact [6] and it has been reported that the apparent damaged area increases monotonically with impact energy [7]. Tolerance to damage is an important requirement in the design and fabrication of composite structural components.…”
Section: Accepted Manuscriptmentioning
confidence: 99%